PENGARUH PEMANFAATAN MEDIA SOSIAL TERHADAP KINERJA PEGAWAI PADA PUSKESMAS LAKESSI KOTA PAREPARE - Hamisa, Nur; Handayani, Sri Rezky (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study examines the impact of social media use on employee performance at the Puskesmas Lakessi, Kota Parepare. The data collection technique used is a questionnaire instrument. The research population consisted of all 80 employees of the Puskesmas Lakessi. The data analysis technique used simple linear regression analysis. The results showed that the use of social media had a positive and significant effect on employee performance.